In The President We Trust: uma análise da concepção religiosa na esfera política dos EUA presente nos discursos de George W. Bush - Marinho, Kleber Maia (2006)
As a whole, the present dissertation lies at the intersection between religion and politics. Religion was embedded in the political scenario of the US at the onset of the nation and, since then, religion and politics have been intertwined into a complex system of coexistence that has strongly influenced the country s destiny. Although the debate regarding the amalgam between religion and politics in the US has been ongoing among the most diverse sectors of information and research, both locally and internationally, it was after the inauguration of George W. Bush and the attacks on 9/11, that such issue gained global repercussion, at a level never before seen in history. In this regard, the present work intends to analyze the relation of historical-cultural, sociological and psychological facts on the political-religious events, particularly those related to the international political scenario, which is hereby represented by the US. Thus, the subject of this investigation focuses on analyzing the presence of religious concepts as found in the speeches of President George W. Bush, during his two terms in office. More specifically, this dissertation examines the phenomena that are deeply rooted in the culture of the United States and have played a key role in supporting Bush s political actions. In this way, it evaluates the degree to which the events on 9/11 served as a bulwark for the religious rhetoric in Bush s discourse and became a tool to legitimate the war against Iraq, his political modus operandi and, ultimately, lead him to reelection. It is therefore concluded that, the ethical, moral and religious factors, deeply set in the culture of the United States throughout its history, together with the trauma caused by the events on 9/11, contributed to the acceptance of Bush s political decisions. The theoretical basis for the work is the hermeneutic methodology, built on a theoretical and bibliographic tripartite design that is sociological, philosophical-linguistic as well as psychological. The first line of investigation is based on the concept of Civil Religion, first developed by Robert Bellah and later expanded by other theoreticians; the second one follows Chaïm Perelman s theory of the New Rhetoric, and the third rests on C. G. Jung s Archetype.